Axial buckling load of partially encased columns under fire – new formulae - Piloto, P.A.G. (2018)
Fire resistance of partially encased columns (HEB and IPE) depends on the temperature evolution during fire exposure. This paper aims to assess de effect of the balanced summation model into the design of the axial buckling load of partially encased columns under fire, according to EN 1994-1-2. New formulae will be proposed to evaluate the fire resistance, based on new simple formulas to determine the flange temperature, the residual height and temperature of the web, the residual cross section and temperature of concrete, the reduced stiffness and strength of reinforcement. ANSYS was used to validate new and safe formulae, based on the analysis of the cross section totally engulfed in fire.